Impact of Endoscopic Ultrasound (EUS) Procedure in Pancreatico-biliary Disorders in Indonesia - Cosmas Rinaldi A Lesmana; Rino Alvani Gani; Irsan Hasan; Andri Sanityoso Sulaeman; Laurentius A Lesmana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2017)
Pancreato-biliary disorders are the challenging disorders in gastroenterology practice. It  is well-known that endoscopic retrograde cholangiopancreatography (ERCP) is a common procedure in managing pancreato-biliary disorders. However, imaging modalities such as abdominal CT scan and MRI has been successfully reduced the unnecessary ERCP to avoid several potential complications. Recently, endoscopic ultrasound (EUS) procedure has become an important tool due to the limitation of imaging modalities in pancreato-biliary disorders. Its ability which is not only for diagnostic, but also for therapeutic purpose has given a new insight for most gastroenterologists in their daily practice. However, the investment, cost, and the proper training curriculum are still debatable in most developing countries, especially in Indonesia.